ANALISIS KONDISI FISIK PADA ATLET TAEKWONDO POOMSE JUNIOR KABUPATEN KOTABARU - Haikal Lyantama Yogha; Rahmadi; Norma Anggara (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
The purpose of this study is to assess junior poomsae taekwondo athletes in Kotabaru Regency with regard to their physical condition. A quantitative approach using tests and measurements as data collecting methods is the methodology employed. 10 athletes who were chosen based on specific criteria made up the research sample. Speed, flexibility, leg strength, agility, and cardiovascular endurance were among the tests that were employed. The majority of the individuals in this research did "fair" to "very good" on the 30-meter sprint speed test, according to the findings. Most of the competitors fell into the "fair" category in the hexagonal agility test. Based on the results of the sit and reach flexibility test, most individuals exhibited a "fair" degree of flexibility. Based on the results of the vertical jump test, most individuals fell within the "fair" and "very poor" groups. In the bleep test, the majority of male and female participants were in the "Fair" category. In conclusion, the physical condition of junior taekwondo poomsae athletes in Kotabaru Regency is generally at a moderate to high level, with some areas that need further improvement. These results can be used as a reference for the development of a more effective and efficient training programme.